BIOLOGIYA TA’LIMIDA TALABALAR EKOLOGIK MADANIYATINI SHAKLLANTIRISHDA INNOVATSION METODLAR - Yadgarova, S.K. (SCIENCE and SOCIETY, 2023)
The article describes the organization of innovative processes, the content and essence of the concepts of "Innovative educational technologies" and "educational innovations", holding environmental days.